Using Artificial Neural Network as an Approach to Analyze People Sentiment Level Based on Social Media Data - Khalid J. Bisher; Abubaker Kashada; Riyadh A. Alsayih; Mohamed Alforgani; Eenas A. Suwayd (Surman Journal of Science and Technology, 2022)
The internet has become an essential online communication tool for many people today. For a variety of reasons, many researches have been done lately in the field of Artificial Neural Network (ANN) considering people sentiments based on social media data. This analytical study conducted to analyze happiness of Libyan people based on twitter data sets. Matlab used in this study to code around 1,000 status/comments data. Processing consists of five processes, namely cleansing, Tokenization, case folding, removal stop word, and stemming. The study represents Artificial Neural Network model for the mining of Twitter opinions using an Artificial Neural Network model approach for the abstracting and visualization scheme of Twitter feeds and a classification and prediction approach. This study presented a contribution in the form of proposing a new visualization model for Twitter mood prediction based on the ANN approach.